2019
DOI: 10.13057/biodiv/d200418
|View full text |Cite
|
Sign up to set email alerts
|

The Isolation and molecular identification of antimicrobial-producing Lactic Acid Bacteria from chao, South Sulawesi (Indonesia) fermented fish product

Abstract: Abstract. Nurhikmayani R, Daryono BS, Retnaningrum E. 2019. Isolation and molecular identification of antimicrobial-producing Lactic Acid Bacteria from chao, South Sulawesi (Indonesia) fermented fish product. Biodiversitas 20: 1063-1068. Chao is traditional fermented fish made of anchovy (Stolephorus sp.), rice, salt, and fermented naturally on controlled environment. The product comes from Pangkep Regency, South Sulawesi. Chao has the potential for the source of high-grade lactic acid bacteria isolates, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
2
16
0
2
Order By: Relevance
“…In addition, their characters were Gram-positive bacteria, rod shape, negative catalase, non-motile, and negative endospore that matched the LAB key characters in Bergey's Manual of Determinative (Brenner et al 2005). Similar LAB characters were also reported by Nurhikmayani et al (2019).…”
Section: The Lab Isolates From Kimchisupporting
confidence: 89%
“…In addition, their characters were Gram-positive bacteria, rod shape, negative catalase, non-motile, and negative endospore that matched the LAB key characters in Bergey's Manual of Determinative (Brenner et al 2005). Similar LAB characters were also reported by Nurhikmayani et al (2019).…”
Section: The Lab Isolates From Kimchisupporting
confidence: 89%
“…Afriani et al (2015), isolated lactic acid bacteria from Bekasam from Jambi, which also has proteolytic activity, namely Lactobacillus pentosus BS15, Lactobacillus plantarum 1 BS22 e Lactobacillus plantarum 1 BL12. Nurhikmayani et al (2019), found Lactobacillus plantarum and Pediococcus pentosaceus from Chao fermented fish from South Sulawesi using 16S rRNA. In addition there are also several sources of lactic acid bacteria from Thai Plaa-som fermented fish products such as Pediococcus pentosaceus, Lactobacillus alimentarius/ farciminis, Weisella confusa, L. plantarum and Lactococcus garviae from Plaa-som, fermented fish products from local producers in Songkhla province, Southern Thailand (Paludan-Mu¨ller et al 2002), Lactococcus garvieae, Streptococcus bovis, Weissella cibaria, Pediococcus pentosaceus, Lactobacillus plantarum, and Lactobacillus fermentum (Kopermsub and Yunchalard 2010), Lb.…”
Section: Results Of 16s Rrna Gene Amplification By Pcrmentioning
confidence: 99%
“…In comparison with previous studies carried out by researches, both of L. plantarum and L. mesenteroides have been isolated from fermented products, (Choi et al 2015;Oguntoyinbo and Narbad 2015;Berbegal et al 2016;Jimenez et al 2018;Lee and Kim 2019;Nurhikmayani et al 2019). Moreover, L. plantarum has also reported from digestive tracts of shrimp (Kongnum et al 2012), human breast milk (Jiang et al 2016) and Italian rye-grass (Vijayakumar et al 2015), whereas, genus of Leuconostoc mesenteroides mainly isolated from meat products (Kaihei et al 2011) and Oreochromis niloticus (Paray et al 2018).…”
Section: Genotypic Identification Lab Producing Bacteriocinmentioning
confidence: 78%